Seeking for Berkah: the Celebration of Kiai Slamet - Fardan Mahmudatul Imamah (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2017)
Abstract One of many annual traditional Javanese ceremony for celebrating the new year is Kirab Kiai Slamet. This ceremony was held in Surakarta, Central Java by one of greatest Javanese Kingdom, Keraton Surakarta Hadiningrat. A thousand visitors who have come from all over of java just to see this ceremony bring various motives. This paper will elaborate how the perspective of Javanese people interprets their attendance on Kirab Kiai Slamet? One of their motives is berkah, then how they perceive this concept of ‘ngalap berkah’? While berkah is one of the most prevalent religious practices in Indonesia, there are various meaning on it from a diverse group. In an effort to reveal the various interpretation of the concept of ‘berkah’, this paper offers an alternative perspective of the study of religion. Because the study of religion is more dominated by world religion paradigm that rigidly defines ‘religion’ as the structured form of religious tradition, an alternative perspective will be needed. After elaborating the experiment of Kirab Kiai Slamet and framed by some theories of religions, this paper will show how ‘indigenous religion paradigm’ have a positive contribution to the enriching of theories of religions in contemporary issues. Keywords: berkah (blessing), Kiai Slamet, world religion paradigm, indigenous worldview.